Artificial Intelligence in Prehospital Tele-Emergency Medicine: A Survey of Acceptance and Attitudes - Nadezhda Durdova; Mathias Schmidt; Hanna Schröder; Pia Thoma; Dominik Groß; Saskia Wilhelmy (Healthcare, 2026)
Background/Objectives: Artificial intelligence (AI) is increasingly being used in medicine to improve the efficiency, accuracy, and timeliness of patient care. In prehospital tele-emergency medicine, AI also has the potential to address various challenges and support tele-emergency physicians. This study focuses on a specific AI-based decision support system being developed for use by practitioners. While technical feasibility is a prerequisite for the successful implementation of this system, social, ethical, and patient-centered considerations are equally important. Methods: The acceptance and perceptions of the German public, as potential patients, regarding the implementation of a specific AI system for prehospital tele-emergency medicine were assessed through an online survey. The results provide qualitative and quantitative insights into participants’ attitudes and acceptance. Results: The perceived advantages and disadvantages of implementing AI in prehospital tele-emergency medicine, as seen by potential patients, were identified, along with moderate acceptance of the technology. Participants emphasized the importance of different factors, including time efficiency, safety, AI recommendation accuracy, responsible system use, data and legal protection, technical stability, and positive impact on physicians’ work and patient outcomes. Conclusions: The findings enhance understanding of public perceptions regarding the use of AI in prehospital tele-emergency medicine and provide a valuable bioethical foundation for guiding the responsible integration of AI into tele-emergency care.